Free energy calculations in biomolecule-nanomaterial interactions - Fu, Hongze; Zhu, Yinbang; Chen, Qu (Frontiers in Physics, 2024)
In computational chemistry and molecular modeling, the interactions between biomolecules (BMs) and nanomaterials (NMs) play a crucial role in various physical and biological processes, and have significant implications in material discovery and development. While there is extensive literature on free energy calculations for drug-target interactions, reviews specifically addressing BM-NM interactions are relatively scarce. This manuscript aims to fill in this gap by presenting a comprehensive overview of the most widely used and well-established methods for free energy calculations. It provides a detailed analysis of the advantages and limitations of these methods and discusses their applicability to BM-NM systems. This work is intended to offer insights into free energy calculations and serve as a guide for future research in this field.